(Distributive laws) For any three sets A, B, C prove that:
I. A∪(B∩C)=(A∪B)∩(A∪C)
[Distirbutive law of union over intersection]
II. A∩[(B∪C)]=(A∩B)∪(A∩C)
[Distributive law of intersection over union]
I. Let x be an arbitary element of A∪(B∩C). Then,
xϵA∪(B∩C)⇒ xϵA or xϵ(B∩C)⇒ xϵA or (xϵB) and xϵC⇒ (xϵA or xϵB) and (xϵA or xϵC)
[∵ 'or' distributes 'and']
⇒ xε(A∪B) and xϵ(A∪C).⇒ xϵ(A∪B)∩(A∪C)
∴ A∪(B∩C)⊆(A∪B)∩(A∪C) …(i)
Again. let y be an arbitary element of (A∪B)∩(A∪C). Then,
yϵ(A∪B)∩(A∪C)⇒yϵ(A∪B) and yϵ(A∪C)⇒(yϵA or yϵB) and (yϵA or yϵC)⇒yϵA or (yϵB and yϵC)
[∵ 'or; distributes 'and']
⇒ yϵA or yϵ(B∩C)⇒ yϵA∪(B∩C)∴ (A∪B)∩(A∪C)⊆A∪(B∩C) …(ii).
From (i) and (ii), we get A∪(B∩C)=(A∪B)∩(A∪C)
II. Let x be an arbitrary element of A∩(B∪C). Then,
xϵA∩(B∪C)⇒xϵA and xϵ(B∪C)⇒xϵA and (xϵB or xϵC)⇒(xϵA and xϵB) or (xϵA and xϵC)
[∵ 'and' distributes 'or']
⇒ xϵ(A∩B) or xϵ(A∩C)⇒ xϵ(A∩B)∪(A∩C)
∴ A∩(B∪C)⊆(A∩B)∪(A∩C) …(iii)
Again, let y be an arbitrary element of (A∩B)∪(A∩C). Then,
yϵ(A∩B)∪(A∩C)⇒yϵ(A∩B) or yϵ(A∩C)⇒(yϵA and yϵB) or (yϵA and yϵC)⇒yϵA and (yϵB or yϵC)
[∵ and' distributes 'or']
⇒yϵA and yϵ(B∪C)⇒yϵA∩(B∪C).
∴ (A∩B)∪(A∩C)⊆A∩(B∪C) …(iv)
From (iii) and (iv), we get A∩(B∪C)=(A∩B)∪(A∩C).